Analysis of Various Computer System Monitoring and LCD Projector through the Network TCP/IP - Budijono, Santoso; Saleh, Robby (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Many electronic devices have a network connection facility. Projectors today have network facilities to bolster its customer satisfaction in everyday use. By using a device that can be controlled, the expected availability and reliability of the presentation system (computer and projector) can be maintained to keep itscondition ready to use for presentation. Nevertheless, there is still a projector device that has no network facilities so that the necessary additional equipment with expensive price. Besides, control equipment in large quantities has problems in timing and the number of technicians in performing controls. This study began with study of literature, from searching for the projectors that has LAN and software to control and finding a number of computer control softwares where the focus is easy to use and affordable. Result of this research is creating asystem which contains suggestions of procurement of computer hardware, hardware and software projectors each of which can be controlled centrally from a distance.